PROCESOS FORMATIVOS DE EXPRESIONES CIUDADANAS EN UNA UNIVERSIDAD MEXICANA - Manuel Ortega, Jorge Isaac (2018)
The present study aimed to understand the formative processes of citizen expressions in students of the campus of social sciences and humanities of Universidad Autónoma de Yucatán (uady). Through a constructionist approach, it is analyzed interviews of 19 students from this institution, through the school year of 2015-2016, finding that matching with peers, the opportunity to discuss social issues and academic training are central processes in the formation of such expressions.